Rising vaule of the british criminal justicesystem: 'Victim-offender mediation' - (:unkn) unknown (My University, 2010)
Çağdaş bir devletin amacı toplumsal barışı sağlamaktır. Toplumsal barışa giden yol da; adalete olan inancın ve güvenin sağlamlaşması, bireyler arasında giderilebilecek çekişmelerin önlenmesi, birbirleriyle davalı bireyler yerine birbirleriyle uzlaşan insanlardan oluşan bir toplum yaratmaktan geçer. İntikam ve hmç duyguları 'adalet'e yabancı kavramlardır. Ceza adaleti sisteminin sunduğu görünüm toplumun gelişmişlik düzeyinin bir aynasıdır. Toplumların gelişim süreci, paralelinde ceza adaletinden beklentileri de değiştirmiştir. Değişen bu beklentilere cevap veremeyen geleneksel ceza adaleti sisteminin taşıdığı eksikliklerin gözlemlenmesi ceza sisteminde değişikliği amaçlayan hareketlerin başlangıç noktası olmuştur. Ceza sistemine yönelik mağdur ve fail kaynaklı tepkilerin artışı, giderek azalan ceza adaleti inancı ile birleşince bu alanda yeni bir arayışa girilmiş ve Onarıcı Adalet anlayışı mekanizmaları ile birlikte hızla yaygınlık kazanmaya başlamıştır. Bu gelişmelerin bir ürünü olarak 20. yüzyılın sonlarına doğru arabuluculuk kurumu onarıcı adaleti uygulayan araçlardan biri olarak cezai meselelerin çözümünde kullanılmaya başlanmıştır. Mağdur-fail arabuluculuğu geleneksel ceza sisteminin göz ardı ettiği bir çok değeri dikkate alarak, gerek mağdur, gerek fail ve gerekse toplum açısından maksimum faydayı hedeflemekte ve sunmuş olduğu bu avantajlar ile çağdaş ceza adaleti anlayışının gerçekleştirilmesinde en etkili araçlardan biri olarak gösterilmektedir.

The path to social peace is aligned with the belief and trust in justice, the prevention of conflicts between individuals and the creation of a community made up of people who are willing to compromise with one another rather than fight. Since the Norman Conquest, the criminal justice system has been dominated by the retributive approach. The development of societies, however, has evolved the expectations from the criminal justice system. Observation of the deficiencies inherent in the traditional criminal justice system has constituted the starting point of the movements aiming to establish a system that can meet those expectations. First, the victimology movement; secondly the reaction against the insufficiency in the correction of the offender and in the reintegration of the condemned into the community through the system of criminal justice; in combination with the community's growing disbelief in the system, caused a change in the approach that is based on the ideas of restorative justice and its mechanisms. As a product of all these developments, victim-offender mediation began to be used towards the end of the 20th century as one of the mechanisms of restorative justice. In these legally supported mediation programmes, numerous values, disregarded by the traditional system, are taken into consideration. This results in maximum benefit for the victim, the offender and the community. Victim-offender mediation is seen as one of the most efficient tools in fulfilling the requirements of modern criminal justice.
Keywords: Hukuk